The Influence of Financial Attitude, Financial Literacy, and Locus of Control on Financial Management Behavior - Stella Maris Juhar Baptista; Andrieta Shintia Dewi (Universitas Pendidikan Ganesha, 2021)
The financial attitude possessed by individuals can be realized because of literacy or knowledge. Meanwhile, the current level of working-age literacy in Semarang City needs to be improved. This background can be seen in the widespread use of credit cards, excessive consumption activities, and the low level of public knowledge about financial institutions and financial products and services. To inhibit this desire, a high locus of control is needed in the individual. This study aims to analyze the influence and relationship between financial attitudes, financial literacy, and locus of control on financial management behavior at working-age in Semarang City. The research method used is the quantitative method with multiple regression analysis. The data collection technique was by distributing questionnaires to four hundred productive age groups in the city of Semarang. The results of this study showed that there was an influence between financial attitudes and financial literacy on partial financial behavior management based on hypothesis testing (t-test), but there is no influence between the locus of control on financial management behavior partially.